The shaping of children’s emotion through literature reading materials - Sujud, Arbaie; Abd Rahim, Normaliza; Mansor, Noraien; Nik Affendi, Nik Rafidah; Salleh, Che Ibrahim; Abdul Rahman, Asiah (The International Journal of Interdisciplinary Social Sciences, 2009)
Emotion needs to exist in every human’s life because without emotion someone’s life tends to be empty and boring. The feelings of happy or sad, cheerful or miserable, hate or love, bravery or cowardice and others that exist in humans’ life will influence the action and perception of daily activities. This means that human life is somehow is affected by the molding of emotion. There are so many ways to implement emotion on someone’s life. In this matter, the differences between the process of molding the emotions of children and adults exist. Children, who spend most of their time at school, will be exposed to a variety of reading materials. The reading materials need to be studied closely to determine the influence of the reading materials on the molding of children’s emotion. Therefore, this paper will discuss the findings of the molding process on childrens’ emotions through the use of literature. This study uses students ranging in age from 7 to12 years old as samples. Thirty students from three primary schools from every zone in Malaysia were chosen for the study. In this matter, the subjects were chosen randomly and were then interviewed. An observation method was used to obtain data in order to fulfill the objectives of the study. Each child’s story was analyzed by using the psycholistic approach. The language aspect (from the books that the subjects read) that influenced the molding process of the childrens’ emotion was taken into consideration throughout the study.